Weighted Fractional Calculus: A General Class of Operators - Fernandez, Arran; Fahad, Hafiz Muhammad (Mdpi, 2022)
We conduct a formal study of a particular class of fractional operators, namely weighted fractional calculus, and its extension to the more general class known as weighted fractional calculus with respect to functions. We emphasise the importance of the conjugation relationships with the classical Riemann-Liouville fractional calculus, and use them to prove many fundamental properties of these operators. As examples, we consider special cases such as tempered, Hadamard-type, and Erdelyi-Kober operators. We also define appropriate modifications of the Laplace transform and convolution operations, and solve some ordinary differential equations in the setting of these general classes of operators.
Keywords: fractional calculus; operational calculus; algebraic conjugation; fractional differential equations; fractional calculus with respect to functions; weighted fractional calculus